Increased Risk of Cesarean Delivery in Severely Obese Patients Who Are Induced Electively or For Obese Status Alone [A212]. (May 2022) - Myers, Brittany A.; Root, Emily A.; Mukherjee, Anish; Gaskins, Jeremy; Pierson, Rebecca C.; Kline, Jessica
Abstract : INTRODUCTION: Prepregnancy obesity is reaching epidemic proportions in the United States. Maternal obesity alone is not an indication for induction of labor (IOL). Recent studies have shown that elective IOL >39 weeks does not increase cesarean delivery (CD) rates; however, patients with severe obesity (BMI >40) are not represented in many of these trials, creating a gap in our ability to provide patient-centered care. METHODS: A retrospective chart review of patients with BMI >40 between May 2016 and December 2020 at a single institution was conducted. Exclusion criteria included: scheduled CD, vaginal birth after cesarean delivery, repeat CD, multiple-gestation pregnancies, delivery <20 weeks, or intrauterine fetal demise. Demographic and other clinical features were analyzed using ANOVA and Fisher tests. The primary outcome was analyzed using linear and logistical regression models. RESULTS: There were 1, 010 deliveries, of which 545 met study criteria. The median BMI was 43.9 (IQR, 41.8–48.5; range, 40.0–92.9). The groups by BMI classification were matched for age, gravida/para, and race. A total of 72.5% of patients were induced during this study period. Of patients who underwent IOL for obesity alone (n=99), 27% delivered via CD, versus 12% for patients who presented in spontaneous labor. Regression models showed significant association between increasing BMI and CD from BMI >40 to BMI 60. CONCLUSION: In patients with BMI >40 who undergo elective induction of labor, there is a significant increase in cesarean delivery rate as opposed to those who present in spontaneous labor.